2015
DOI: 10.1016/j.postharvbio.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ambient loading of citrus fruit into reefer containers for cooling during marine transport using computational fluid dynamics

Abstract: Defraeye T., Cronjé P., Verboven P., Opara U.L., , Exploring ambient loading of citrus fruit into reefer containers for cooling during marine transport using computational fluid dynamics, Postharvest Biology and Technology 108, 91-101. AbstractA promising cold-chain protocol is explored as an alternative to the commonly-used forced-air pre-cooling (FAC) of citrus fruit prior to shipping: ambient loading of fruit in reefer containers for cooling during long-haul marine transport. Despite the multiple logistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…During the past decade, however, a few studies were carried out to explore the potential of ambient loading into reefers, for cooling during long‐haul sea transportation, as an alternative to forced‐air precooling of produce before it is loaded into the reefer. Defraeye and others (, ) explored the potential of this cold chain protocol for the ambient loading of citrus fruit, while Jedermann and others (, ) explored it for the banana chain. Ambient loading reduces the time and cost required to handle and precool the pallets at precooling facilities.…”
Section: Temperature Conditions Along the Cold Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past decade, however, a few studies were carried out to explore the potential of ambient loading into reefers, for cooling during long‐haul sea transportation, as an alternative to forced‐air precooling of produce before it is loaded into the reefer. Defraeye and others (, ) explored the potential of this cold chain protocol for the ambient loading of citrus fruit, while Jedermann and others (, ) explored it for the banana chain. Ambient loading reduces the time and cost required to handle and precool the pallets at precooling facilities.…”
Section: Temperature Conditions Along the Cold Chainmentioning
confidence: 99%
“…It can also reduce postharvest losses when applied immediately after palletization, since the cold chain starts earlier than when precooling occurs at the harbor, as transport to those facilities is often unrefrigerated. However, CFD simulations (Defraeye and others ) showed that the fruit cooling rate with ambient loading into reefers is slower in comparison with forced‐air precooling. Also, the cooling heterogeneity between different layers of boxes (in height) and between individual fruits in a single box is larger for ambient loading.…”
Section: Temperature Conditions Along the Cold Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…CFD is a method that using numerical, physical analysis and computational software solves and analyses problems related to fluid flows (air mixtures and liquids). Recently, Defraeye et al [59] suggested an innovative and promising cold-chain protocol alternative to the commonly used forcedair pre-cooling (FAC) of citrus fruit prior to shipping. The theoretical approach, by means of computational fluid dynamics (CFD), explored ambient (warm) loading of citrus fruit into refrigerated containers (reefer) for cooling by vertical airflow during marine transport.…”
Section: Citrus Shipmentmentioning
confidence: 99%
“…Precooling and storage are very important part of the cold chain (Kumar et al, 2008;Norton et al, 2013), nonetheless, not too much attention is paid in the transport (James et al, 2006), if it is taken into account that the fresh produce suffer transport distances above several thousand kilometers (Jedermann et al, 2011a;Jedermann et al, 2011b). There is room for improvement and optimization in new protocols during the transportation (Defraeye et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%